PENGARUH PROFITABILITAS, LIKUIDITAS, UKURAN PERUSAHAAN, KEPEMILIKAN MANAJERIAL, DAN KEBIJAKAN HUTANG TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN SEKTOR PERTANIAN YANG TERDAFTAR DI BEI PERIODE 2013-2015 - NOVIANTO, ARISKI (Jurnal Ilmu Manajemen (JIM), 2017)
Along with the development of capital markets in economic progress, investment activities conducted by investors have a goal to seek income from dividends. Generally every company in distributing dividends should consider partial retention of profits to be reinvested as a more profitable business opportunity. The dividend policy is influenced by several factors, namely, profitability, liquidity, firm size, managerial ownership and debt policy. Given the phenomenon shows the dividend policies that run each company vary. What will be done in this research is to know the effect of profitability, liquidity, firm size, managerial ownership and debt policy to dividend policy in Indonesia Stock Exchange period 2013-2015 by using logistic regression. Simulation is done with quantitative data obtained from the annual financial report published by IDX (Indonesia Stock Exchange) for three years from 2013 until 2015. So that the result that profitability only influence the dividend policy while other factors that is liquidity, size Companies, managerial ownership and debt policy have no effect on dividend policy. Keywords: profitability, liquidity, size of firm, managerial ownership, debt policy